PURISTS. (The Accounting Review, 1930)
Abstract This article focuses on the recommendations by an accountants, in public practice on the definition on earned surplus. This accountant meant phraseology according to the evidence in his suggestions. It is probable that the majority of persons who have been observed misusing the word mean diction. An aberration on the part of every accountant whom have been heard using the term is the mispronunciation of amortize and amortization. It is said that the accent of the first word and the secondary accent of the second word are on the second syllable.